2001
DOI: 10.1021/jp002379h
|View full text |Cite
|
Sign up to set email alerts
|

DFT Modeling of Chemical Vapor Deposition of GaN from Organogallium Precursors. 1. Thermodynamics of Elimination Reactions

Abstract: The thermochemistry of dissociation and elimination reactions of organogallium precursors for the GaN chemical vapor deposition (CVD) is studied at the hybrid Hartree-Fock/density functional level of theory (B3LYP/pVDZ). Geometries, relative energies, vibrational frequencies of R x GaNR′ x species, and their dissociation products (NR x , GaR x , x ) 1-3; (R, R′ ) H, CH 3 ) are presented. Methane elimination from the source adducts is exothermic at standard conditions, while hydrogen elimination is endothermic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 82 publications
6
53
0
Order By: Relevance
“…Further CH 4 elimination and association (oligomerization) may occur, eventually leading to clusters (or nuclei) large enough to support growth by a CVD process. One aspect of the concerted path-A is that it involves reactions with relatively low activation energy (o40 kcal/mol) [12][13][14][15]. Mihopolous et al [12] used a mechanism of this type, with thermophoresis considerations, to explain many AlN OMVPE observations.…”
Section: Introductionmentioning
confidence: 99%
“…Further CH 4 elimination and association (oligomerization) may occur, eventually leading to clusters (or nuclei) large enough to support growth by a CVD process. One aspect of the concerted path-A is that it involves reactions with relatively low activation energy (o40 kcal/mol) [12][13][14][15]. Mihopolous et al [12] used a mechanism of this type, with thermophoresis considerations, to explain many AlN OMVPE observations.…”
Section: Introductionmentioning
confidence: 99%
“…The strong intramolecular H-Cl hydrogen bonding and dipoledipole interactions are known to favor the formation of larger oligomer species [21]. The extent of the oligomerization process has not been known explicitly, but Timoshkin reported that the generation of gas phase [HGaNH] n clusters even with oligomerization degree n ≥ 60 is viable in his theoretical works [30,31]. When the Cl/In ratio becomes much higher than 3, InN growth becomes unfavorable because of the enhanced HCl etching by excess HCl (g).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the majority of computational investigations have dealt with the chemistry of ammonia adducts and their decomposition products. A wealth of thermodynamic information has been calculated at the DFT level by Timoshkin et al [80][81][82]. The structures and relative energies of a number of possible non-radical gas phase species have been calculated, including gallium amides R 2 GaNR 2 (with R, R = Me, H) and their oligomers.…”
Section: Theoretical Modeling Of Omvpementioning
confidence: 99%